Bacterial and fungal seasonality in the rhizosphere of two species of plants in the semiarid Valley of Zapotitlán, Puebla - Soto Aquino, Hilda Ventura; Zavala Hurtado, José Alejandro; Pérez Moreno, Jesús; Camargo Ricalde, Sara Lucía (Revista Mexicana de Ciencias Agrícolas, 2018)
In the arid and semiarid systems the vegetation is distributed in patches. Associated to this patches, microorganisms exist that participate in the transformation of organic and mineral compounds that influence the content and mobility of the macro and micro elements, as in the balance and assimilation by plants and therefore important for their growth (Vega et al., 2010). In this study were quantified the bacterial and fungal populations in the rhizosphere of two species of plants with different levels of invasiveness in three vegetation patches from Valle de Zapotitlan, in the state of Puebla. The method of successive dilutions was used to quantify the microbial populations. The results showed that the microbial populations were affected by the physical and chemical conditions of the soil y by the plant species. Additionally, the populations of rhizospheric microorganisms associated to the plants of Viguiera dentada and Ferocactus latispinus were differentially affected by seasonality. The microbiological total count of bacterial and fungal can be used in studies on invasiveness of the ecosystem, by showing in terms of its abundance that are sensitive to the type of plants and weather.
Keywords: Ferocactus latispinus; Viguiera dentata; invasive plants; microorganisms